Evaluation of the Net Wealth in Bulgaria Using Data from the Global Wealth Databook of Shorrocks et al. (2023) - Peshev, Petar (Research Papers, 2024)
This research paper estimates the net wealth of an adult in Bulgaria, using data of Shorrocks et al. (2023). Net wealth per adult has a strong functional relationship with GDP per adult, corresponding on average to four times GDP per adult. Econometric research suggests net wealth per adult equals between $56,989 and $66,373. Net wealth is most sensitive to changes in wealth, in the form of real assets and to a lesser extent, to financial wealth and debt, and to changes in GDP per adult and the rate of change of the elderly population.
Keywords: Regression analysis; Net worth per adult; Wealth in bulgaria; Wealth modelling